Holding Robots Responsible: The Elements of Machine Morality. Issue 5 (May 2019) - Bigman, Yochanan E.; Waytz, Adam; Alterovitz, Ron; Gray, Kurt
Abstract : As robots become more autonomous, people will see them as more responsible for wrongdoing. Moral psychology suggests that judgments of robot responsibility will hinge on perceived situational awareness, intentionality, and free will, plus human likeness and the robot's capacity for harm. We also consider questions of robot rights and moral decision-making.